The evolution of irreversible cell differentiation under cell death effect - Yuanxiao Gao; Xueyan Zhao; Caixia Li (PLoS ONE, 2025)
Cell differentiation is an important characteristic of multicellular organisms which produce new-typed cells to engage in diverse life functions. Irreversible differentiation, as an important differentiation pattern, describes cells differentiated by determined trajectories to form specialized cell types. It has been found that differentiated cell types often show different death rates. Yet, it is still unclear what role cell death plays in shaping the formation of irreversible cell differentiation. Here, we establish a theoretical model to investigate the impact of cell death on the evolution of irreversible cell differentiation in multicellular organisms. Irreversible differentiation refers to the loss of a cell type’s differentiation potential, and it is constructed by the sequences of differentiation probabilities of a cell type across cell divisions. We show that irreversible differentiation is more likely to occur when cell death rates between cell types are linear. Meanwhile, differences in death rates between cell types affect the emergence conditions of irreversible differentiation, whereas no significant impacts on that from equal cell death rates. Additionally, we found that cell death impacts the cell number and cell composition of a mature organism. These findings provide insights into understanding the role of cell death in the formation of cells’ irreversible differentiation.